2019
DOI: 10.1080/13102818.2018.1561210
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure ofToona ciliatarevealed by simple sequence repeat markers

Abstract: Toona ciliata (Meliaceae) is a rare, fast-growing commercial tree species that produces red timber with beautiful grains. It used to be widely distributed in the past, but few natural forests exist in the field now. Here, we tested 12 nuclear microsatellite markers derived from 551 individuals of 29 populations in China, and investigated the genetic diversity and population structure in T. ciliata. Our results revealed 146 alleles obtained from all of the populations studied here, with an average polymorphic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Nevertheless, the findings of the present study indicate that at the level of both species and variety, there appears to be relatively low genetic diversity among the three species Z. bungeanum, Z. armatum, and Z. piperitum. Moreover, we were unable to detect any substantial regional variation, which can probably be attributed to the parthenocarpic mode of reproduction, which is a notable characteristic of these species and has been widely investigated in other species [26]. Apomixis is considered a primary factor contributing to this category of result, and because reproduction in most Zanthoxylum species occurs via apomixis, this is probably a key factor associated gene stability and low genetic diversity.…”
Section: Genetic Diversity Assessmentmentioning
confidence: 68%
“…Nevertheless, the findings of the present study indicate that at the level of both species and variety, there appears to be relatively low genetic diversity among the three species Z. bungeanum, Z. armatum, and Z. piperitum. Moreover, we were unable to detect any substantial regional variation, which can probably be attributed to the parthenocarpic mode of reproduction, which is a notable characteristic of these species and has been widely investigated in other species [26]. Apomixis is considered a primary factor contributing to this category of result, and because reproduction in most Zanthoxylum species occurs via apomixis, this is probably a key factor associated gene stability and low genetic diversity.…”
Section: Genetic Diversity Assessmentmentioning
confidence: 68%
“…Pollen flow of T. ciliata could be mainly entomophilous, and seed dispersal is mainly mediated by wind together with birds 9 , with an anticipation of a certain level of population genetic differentiation. Previous studies demonstrated that population differentiation of T. ciliata was substantially large, with F st = 0.792 among range-wide populations assayed with nuclear SRAP 13 and 0.324 with nuclear SSR loci among 29 populations 4 . The present study also indicated significant genetic differentiation (F st = 0.345) among the six populations, and detected significant IBD effects among the six populations.…”
Section: Sample Sizes and The Number Of Locimentioning
confidence: 96%
“…The present study also indicated significant genetic differentiation (F st = 0.345) among the six populations, and detected significant IBD effects among the six populations. Zhan et al 4 showed that IBD effects were absent among populations in the western part but present in the eastern part. IBD effects among populations could likely affect mating system since mating systems differed in different regions under significant IBD effects 29 .…”
Section: Sample Sizes and The Number Of Locimentioning
confidence: 99%
See 2 more Smart Citations